Time course of changes in ocular wavefront aberration after administration of eye ointment - Hiraoka, T (Nature Publishing Group, 2012)
PURPOSE: To investigate the influence of an eye ointment on ocular aberration. DESIGN: Prospective, comparative study. METHODS: In 10 normal volunteers, ocular aberration was assessed before and 5, 30 min, 1, 2, 3, 6, and 12 h after administration of ofloxacin eye ointment. Ocular aberration was sequentially measured over a period of 10 s, and the root mean square (RMS) of the second-, third-, fourth-, and total higher-order aberrations (HOAs) were determined. From the sequential changes in total HOAs during 10 s, the fluctuation index (FI) and stability index (SI) were calculated. The obtained data were compared with those of another 17 normal volunteers who received timolol maleate gel-forming ophthalmic solution. RESULTS: No significant changes in second-order RMS were observed after administration of the ointment. HOAs such as third-, fourth-, and total higher-order RMS significantly changed during the study period (P<0.05, repeated-measures analysis of variance). The RMS of each HOA component significantly increased 5 min after administration compared with the baseline values (P<0.05, Dunnett test). FI also increased significantly 5 min after administration (P<0.05), but SI did not change significantly. When compared with the results of the gel-forming solution group, HOAs and FI showed significantly higher values at several time points during 6 h after application (P<0.05, Mann–Whitney U-test). CONCLUSIONS: Administration of eye ointment significantly degrades optical quality of the eye by increasing and oscillating HOAs. These changes were more pronounced than those after instillation of gel-forming ophthalmic solution for at least several hours.